2021
DOI: 10.1111/bcp.14826
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation as an adjunct therapy for COVID‐19: Challenges and opportunities

Abstract: An outbreak of a novel coronavirus (COVID-19 or 2019-CoV) infection has posed significant threats to international health and the economy. Patients with COVID-19 are at risk of cytokine storm, acute respiratory distress syndrome (ARDS), reduced blood oxygenation, mechanical ventilation, and a high death rate. Although recent studies have shown remdesivir and dexamethasone as treatment options, there is an urgent need to find a treatment to inhibit virus replication and to control the progression of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 97 publications
(300 reference statements)
0
56
0
Order By: Relevance
“…Zinc's many antiviral, immunomodulatory and anti-inflammatory functions have generated a lot of interest for its potential use in COVID-19 management (8,13,49,50,77). Consequently, over 50 RCTs including zinc, albeit typically used as adjuvant treatment or prophylactic, have commenced (ClinicalTrials.Gov, September 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zinc's many antiviral, immunomodulatory and anti-inflammatory functions have generated a lot of interest for its potential use in COVID-19 management (8,13,49,50,77). Consequently, over 50 RCTs including zinc, albeit typically used as adjuvant treatment or prophylactic, have commenced (ClinicalTrials.Gov, September 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There, the initial hypozincemia and hyposelenemia is thought to stem from disease-driven inflammatory process (acute phase response), is found chiefly in plasma (but not e.g. erythrocytes) (13,89,90) and recovers over time in survivors. However, this does not mean that pre-existing deficiencies will not have a compounded negative impact at this stage (50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Zinc is a group IIb metal that is involved in diverse physiological processes such as growth, immune system modulation and tissue repair, and it acts as antiinflammatory agent and can promote wound healing. 6 Zinc has been shown to be effective in the prevention of oral mucositis, xerostomia, and pain associated with chemotherapy. 7 A recent oncologic study showed zinc lozenge, showing a significant reduction in the use of https://doi.org/10.18231/j.jds.2021.004 2320-7302/© 2021 Innovative Publication, All rights reserved.…”
Section: Introductionmentioning
confidence: 99%